Response of Drought-Stressed Grafted and Nongrafted Tomato to Postemergence Metribuzin. (31st May 2017) - Chaudhari, Sushila; Jennings, Katherine M.; Monks, David W.; Jordan, David L.; Gunter, Christopher C.; Louws, Frank J.
Abstract : Tomato grafting is practiced worldwide as an innovative approach to manage stress from drought, waterlogging, insects, and diseases. Metribuzin is a commonly used herbicide in tomato but has potential to cause injury after application if plants are under stress. The influence of metribuzin on grafted tomato under drought-stress has not been studied. Greenhouse experiments were conducted in Raleigh, NC to determine the tolerance of drought-stressed grafted and non-grafted tomato to metribuzin. The tomato cultivar 'Amelia' was used as the scion in grafted tomato, and for the non-grafted control. Two hybrid tomato 'Beaufort' and 'Maxifort' were used as rootstocks for grafted plants. Drought-stress treatments included: no drought-stress; 3 d of drought-stress before metribuzin application with no drought-stress after application (3 d DSB); and 3 d of drought-stress before metribuzin application with 3 d of drought-stress after application (3 d DSBA). Metribuzin was applied at 550 g ai ha −1 . No difference in injury from metribuzin was observed in grafted and non-grafted plants. However, at 7 and 14 d after metribuzin treatment (DMT), less injury was observed on tomato in the 3 d DSBA treatment (5 and 2% injury, respectively) than on plants in the 3 d DSB treatment (15 and 8% injury, respectively) or those that were never drought-stressed (18 and 11% injury, respectively). Photosynthesis and stomatal conductance measured prior to metribuzin application were reduced similarly in grafted and non-grafted tomato subjected to drought-stress. Photosynthesis and stomatal conductance of grafted and non-grafted tomato at 7 DMT was not different among drought-stress treatments or metribuzin treatments. Grafted and non-grafted tomato plants under drought-stress exhibit similar tolerance to metribuzin. The risk of metribuzin injury to grafted tomato under drought-stress is similar to non-grafted tomato.